Kajian Dampak Perambahan Hutan Terhadap Struktur Komposisi serta Status Regenerasi pada Kawasan Hutan Lindung Roko Raka Matalumbu (Studi Kasus Hutan Lindung di Desa Reda pada Kecamatan Wewewa Barat Kabupaten Sumba Barat Daya) - Sukartino Habamananga; Ludji Michael Riwu Kaho; Nixon Rammang (Wana Lestari, 2024)
Forests play an important role in maintaining the stability of the environment, the balance of flora and fauna ecosystems, and also as a source of water system support. The Roko Raka Matalumbu Protected Forest in Reda Pada Village is very rampant in encroachment activities carried out by the surrounding community to be used as plantation land, agriculture, timber harvesting and other forms of utilization. The negative impact of encroachment is one of the changes in the structure of vegetation composition and also to the status of forest regeneration. This study aims to analyze the composition structure and regeneration status in the Roko Raka protected forest area. The methods used in this research are qualitative and quantitative methods. Quantitative data was obtained from vegetation analysis, while qualitative data collection was carried out in four ways namely; literature study, interviews, observation and documentation. The results of vegetation analysis of tree growth rates amounted to 0.31 individuals / ha, poles amounted to 1 individual / ha, saplings amounted to 0.76 individuals / ha, and seedlings amounted to 68 individuals / ha. The horizontal structure in this protected forest area is dominated by the 30-40 cm diameter age class and the vertical structure is dominated by stratum B (20-30 cm). The Regeneration Status of the Roko Raka Protected Forest based on tree species has the status of "No regeneration". Based on the results of interviews with the Government and the Community, it is known that forest encroachment by the community is the main reason for the decline in the structure and composition of the Roko Raka Protection Forest. Keywords : Encroachment, Composition Structure, Regeneration Status, Roko Raka Matalumbu Protection Forest